Electrocoagulation in Wastewater from Spent-Batteries Recycling - Mufakhir, Fika Rofiek; Khotimah, Chusnul; Oediyani, Soesaptri; Astuti, Widi; Sumardi, Slamet; Prasetia, Hendra; Arham, La Ode; Hakim, Hafid Zul; Petrus, Himawan Tri Bayu Murti; Poernomo, Venny (Indonesian Journal of Chemistry, 2024)
This study uses electrocoagulation to investigate reducing heavy metal content in wastewater from discharging spent batteries. ICP-OES analysis shows that heavy metals exceed the environmental water standard. The electrocoagulation procedure was conducted within a reactor with a 500 mL volume and a rectifier with a 5 A current capacity. Three types of electrode material combinations were used: iron (Fe) and aluminium (Al) as well as Fe-Fe, Al-Al, and Fe-Al pairs with 1 cm in the distance by parallel monopolar cells. Alternating current was used with 30, 40, and 50 A/m2 current density. The best result shown in the Fe-Al electrode pair combination system at 40 A/m2 for 30 min contact time and removal efficiencies for Co, Cd, Ni, Zn, and As is 98.76, 90.73, 99.32, 97.93, and 97.78%, respectively, while for Hg it is 31.84%, even though only Cd is above the standard limit. The heavy metal bearing was confirmed using SEM-EDS in the floc and the precipitate residue. The dissolved electrode materials and electrical energy consumed are 0.32 g and 0.109 kWh/m3, respectively. This method can be a good alternative for treating wastewater compared to direct current electrocoagulation, where the electrode and energy will be less consumed.